EKSPERIMENTASI MODEL PEMBELAJARAN KOOPERATIF STAD DENGAN AUTOGRAPH DITINJAU DARI SIKAP PERCAYA DIRI DAN KREATIVITAS SISWA KELAS VIII SMP DI KABUPATEN MAGETAN TAHUN AJARAN 2013/2014 - Agus Siswanto, Fransiskus Xaverius; Sujadi, Imam; Roswitha, Mania (Jurnal Pembelajaran Matematika, 2016)
Abstract: The aim of this study was to determine and compare cooperative learning model of STAD by AutoGraph and STAD viewed of self-confidence and creativity. This study was a quasi experimental research with 2x2x2 factorial design. The population of this study was all students of junior high school in Magetan Regency in academic year 2012/2013. Sampling was done by stratified cluster random technique. The total of sample was 172 students, with details of 86 students for first experiment class and 86 students for second experiment class. The instruments used to collect data were test of prior knowledge in mathematics, self-confidence questionnaire, creativity questionnaire and mathematics achievement test. The balance test of students prior knowledge in mathematics data used t-test and concluded that two of experimental classes have balance prior knowledge in mathematics. The testing of hypothesis used three-way analysis of variance with unballanced cell. The testing of hypothesis concluded as follows. (1) The students who taught by cooperative learning model of STAD by AutoGraph type have same mathematics achievement than students who taught by cooperative learning model of STAD type. (2) The students who have high self-confidence have better mathematics achievement than students who have low self-confidence. (3) Students who have high creativity have better mathematics achievement than students who have low creativity. (4) There was an interaction between learning model and self-confidence toward mathematics achievement. The students taught by cooperative learning model of STAD by AutoGraph type and who have high self-confidence have better mathematics achievement than the students who have low self-confidence. (5) There was no an interaction between learning model and creativity toward mathematics achievement. (6) There was no an interaction between self-confidence and creativity toward mathematics achievement. (7) There was an interaction between learning model, self-confidence and creativity toward mathematics achievement. The students taught by cooperative learning model of STAD type and who have low self-confidence and high creativity have better mathematics achievement than the students who have low creativity.Keyword: STAD by Autograph, STAD, Self-Confidence, Creativity, Mathematics Achievement.